Outcome of Management of Midshaft Clavicular Fractures with Titanium Elastic Nail System: A Case Series - Karthik Chithartha; Vanasekar Mokkasamy (Journal of Orthopedics and Joint Surgery)
Introduction: The management of displaced midshaft clavicular fractures (MSCFs) is still a constant debate, and the current trend toward minimally invasive osteosynthesis has led us to study this technique and the outcome of stabilization using the titanium elastic nail system (TENS). Materials and methods: A total of 15 patients with fractures of the midshaft of the clavicle managed with TENS were included in the study from January 2018 to December 2022. Intraoperatively, TENS nail was applied for 11 cases with closed reduction, whereas four cases went on to have open reduction. All patients were followed for a minimum of 6 months postoperatively (post-op) with radiographs and functional score assessment. Result: The average age of the study population was 38.8 ± 11 years. Eight patients had AO type A fracture, five patients with type B, and two patients with type C fracture. Clinical assessment of the patients was done after radiological union using the constant shoulder score. The clinical union was attained in 4–7 weeks, while the radiographic union was attained in 6–9 weeks. In this study, we noticed that patients with type C fracture took longer for fracture union and mild medial migration of nails at final follow-up, requiring implant exit after fracture union. Conclusion: Surgical stabilization with TENS showed better results for patients with type A and B midclavicular fractures with respect to early functional recovery, minimally invasive, less operative time, and early mobilization. Clinical significance: Since the outcome of managing simple displaced MSCs using TENS is relatively excellent according to our study, TENS can be used to manage type A and B MSC fractures since it is easily available, less invasive, leaves a smaller scar, and has a faster recovery.